Membrane and protein dynamics in live plant nuclei infected with Sonchus yellow net virus, a plant-adapted rhabdovirus - Goodin, Michael M.; Chakrabarty, Romit; Yelton, Sharon; Martin, Kathleen; Clark, Anthony; Brooks, Robert (Journal of General Virology, 2007)
Sonchus yellow net virus (SYNV) serves as the paradigm for the cell biology of plant-adapted rhabdoviruses. Fluorescence recovery after photobleaching (FRAP) demonstrated that SYNV-induced intranuclear membranes are contiguous with the endomembrane system. Fluorescence intensity measurements of a green fluorescent protein-tagged nuclear envelope marker were consistent with electron microscopy studies, which suggest that infection by SYNV results in invagination of the inner nuclear membrane. Fusions of a red fluorescent protein to five SYNV-encoded proteins were used to determine the relationship between virus-induced intranuclear membranes and the localization of viral proteins. These data establish definitively that localization in the context of infected cells provides a superior means to predict protein function compared with localization studies conducted in mock-inoculated cells. Substructure has been identified within the viroplasm, the putative site of virus replication, which suggests that the nucleocapsid (N) protein occupies a region at the junction between the viroplasm and intranuclear membranes that largely excludes the phosphoprotein. Within virus-infected nuclei, the SYNV matrix (M) protein and glycoprotein (G) were associated predominantly with membranes, whereas sc4, the predicted movement protein, accumulated primarily at punctate loci on the periphery of cells. Coexpression of differently tagged SYNV protein fusions in combination with FRAP analyses suggest a model whereby the replication and morphogenesis of SYNV are spatially separated events. Finally, an M protein-containing complex was discovered that appears to bud from the nucleus and that moves on ER membranes. Taken together, these data represent the most comprehensive analyses of rhabdoviral protein localization conducted in the context of infected cells.